Analysis of Stock Investment Decisions through Price Earnings Ratio (A Case Study on Construction Service Companies) - Dio Alfarago; Luthfi Aziz Bakhtiyar (Universitas Batanghari, 2023)
The objective of this study is to analyze investment decisions using the Price Earnings Ratio (P/E Ratio) approach. The sample companies for this study are construction service companies that areÂ listed on the Indonesia Stock Exchange in 2021. This study combines descriptive and quantitative methods. The results indicated that PT. Waskita Karya Tbk., PT. Wijaya Karya Tbk., PT. Adhi Karya Tbk., and PT. Pembangunan Perumahan Tbk. are sequentially the companyÂ with the highest investment priority. This priority scale can be taken into account by investors when making investments.